Current management strategies of urachal anomalies in pediatric patients: A scoping review - Ghattas, Yasmine S.; Gelikman, David G.; Ibanez, Kristen R.; Ellsworth, Pamela; Seth, Abhishek (Frontiers in Urology, 2023)
Introduction: Management of urachal anomalies in pediatric patients has historically lacked a clear consensus between conservative and surgical management. To review and summarize the literature on the diagnosis, symptoms, and evolution in the management of urachal anomalies in pediatric patients. Methods: We performed a critical literature review of PubMed/Medline and the WebOfScience in July 2022 from January 2000 to February 2022. Results: 32 publications were selected for inclusion in this analysis.1,438 unique studies were identified with 32 studies meeting inclusion criteria. 15/32 studies discussed both conservative and surgical management, 14/32 studies discussed only surgical management outcomes, and 3/32 studies discussed diagnostic methods. The studies discussing conservative management supported the treatment of urachal anomalies with an initial conservative approach, which includes watchful waiting, repeated ultrasounds, lesion measurement, and antibiotic use. 5/32 of the included studies identified patients that were converted from conservative to surgical management with conversion rates ranging from 12.5% to 43.5% per study. 14/20 converted patients were identified to have a urachal cyst and 13/20 had a persistent infection. Conclusions: Strong evidence exists that supports initial conservative management over surgical management of pediatric urachal anomalies. However, predictive factors for determining which patients will require surgical management remain elusive. Treatment algorithms can potentially be developed once carefully developed prospective studies delineate statistically significant patient factors which necessitate surgical management over observation.